Stereoselective synthesis of β-(hydroxymethylaryl/alkyl)-α-methylene-γ-butyrolactones. - Hodgson, D; Talbot, E; Clark, B (2011)
Zinc or a chromium(II) source with 3-(bromomethyl)furan-2(5H)-one (3) and an aldehyde gives β-(hydroxymethylaryl/alkyl)-α-methylene-γ-butyrolactones 5 in good yields and high diastereoselectivities. The methodology is demonstrated in concise syntheses of (±)-hydroxymatairesinol (8) and (±)-methylenolactocin (10) by subsequent arylboronate conjugate addition and translactonization, respectively.